2011
DOI: 10.1007/s00464-011-1789-8
|View full text |Cite
|
Sign up to set email alerts
|

Carbon dioxide insufflation during endoscopic retrograde cholangiopancreatography reduces bowel gas volume but does not affect visual analogue scale scores of suffering: a prospective, double-blind, randomized, controlled trial

Abstract: Background Endoscopic retrograde cholangiopancreatography (ERCP) and related

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(40 citation statements)
references
References 17 publications
5
35
0
Order By: Relevance
“…These results were similar to those of a trial performed in patients undergoing gastric ESD [6] , namely, CO2 insufflation reduces bowel gas volume but not procedure-related pain and discomfort. Although most trials concerning CO2 insufflation during various kinds of endoscopic procedures have demonstrated a reduction of pain and discomfort [2][3][4][5] , some randomized trials in endoscopic retrograde cholangiopancreatography have reported that CO2 insufflation was not effective in reducing procedure-related pain [20,21] , the same as in this trial. Most of the patients in this trial had no pain after the procedure and the mean VAS scores of pain and distension were consistently low not only in the CO2 group but also, unexpectedly, in the Air group.…”
Section: Discussionmentioning
confidence: 59%
“…These results were similar to those of a trial performed in patients undergoing gastric ESD [6] , namely, CO2 insufflation reduces bowel gas volume but not procedure-related pain and discomfort. Although most trials concerning CO2 insufflation during various kinds of endoscopic procedures have demonstrated a reduction of pain and discomfort [2][3][4][5] , some randomized trials in endoscopic retrograde cholangiopancreatography have reported that CO2 insufflation was not effective in reducing procedure-related pain [20,21] , the same as in this trial. Most of the patients in this trial had no pain after the procedure and the mean VAS scores of pain and distension were consistently low not only in the CO2 group but also, unexpectedly, in the Air group.…”
Section: Discussionmentioning
confidence: 59%
“…All monitoring parameters and level of sedation were recorded by trained sedation nurses every 5 min. We did not directly measure arterial pCO 2 or transcutaneous pCO 2 measurements based on previous results . After completion of the endoscopic procedure, patients were transferred to the recovery unit for continued hemodynamic monitoring.…”
Section: Methodsmentioning
confidence: 99%
“…4,5,22 A few RCTs have suggested that CO 2 insufflation did not reduce procedure-related pain measured by using VASs. [28][29][30] However, only a few studies have evaluated CO 2 insufflation during endoscopic resection. Most studies did not focus on procedure-related pain but rather on safety and feasibility.…”
Section: Discussionmentioning
confidence: 99%